The Influence of Tensile Strength Difference with Variable Gravel Sizes on the Hydraulic Fracture Propagation in the Conglomerate Reservoir. (17th February 2022) - Chen, Junnian
Abstract : Conglomerate reservoir is a representative reservoir of unconventional oil and gas resources, and hydraulic fracturing is also used to increase its production. However, the tensile strength of conglomerates with different sizes is various, which has an important impact on the hydraulic fracture propagation in the conglomerate reservoir. To study the tensile strength difference caused by the size of conglomerate gravel, some Brazilian splitting tests were conducted. To find the influence of tensile strength difference on the hydraulic fracture propagation, some true triaxial hydraulic fracturing experiments for layered formations were carried out. The concept of the fracture element in conglomerate formations was proposed. The results showed the following: (i) the tensile strength of conglomerate rock decreased with the increase of the gravel size, and the average tensile strengths of specimens with gravel diameters of 2.0–6.0 mm and 6.0–20.0 mm were 65.5% and 43.6% of that with 0.1–2.0 mm diameter, respectively; (ii) hydraulic fractures easily deflected at the interface of fine-grained conglomerate and medium-grained conglomerate; (iii) hydraulic fractures were prone to propagate to the layers with larger gravel sizes, and the smaller the gravel size, the lower the penetration probability. It is helpful to increase the understanding of the hydraulic fracture propagation under different gravel sizes in the conglomerate reservoir, and it can provide a reference for well distribution and hydraulic fracturing design.